Morphogenic effects of ramihyphin A in filamentous fungi - Baráthová, H; Betina, V; Baráth, Z; Nemec, P (Folia microbiologica, 1975)
Ramihyphin A at subfungistatic concentrations stimulates ramification of hyphae of filamentous fungi. Stimulation of terminal ramification of hyphae that can be observed particularly in phytopathogenic fungi is most frequent. Hyphae of Microsporon canis, Trichophyton mentagrophytes, Blastomyces dermatitidis, Coccidioides immitis and Histoplasma capsulatum ramify intensively laterally. Stimulation of the lateral ramification was observed in Monilia fructigena, Penicillium marneffei and Penicillium chrysogenum. The antibiotic induces also formation of vesicular structures in phytopathogens. Due to the substantial ramification of hyphae, both terminal and lateral, the growth of colonies is interrupted. The addition of the antibiotic to a growing colony of Botrytis cinerea induces dichotomic ramification of terminal hyphae after 3 h of growth. Lateral hyphae begin to grow later and further ramify dichotomically. Dense bundles of ramified hyphae are formed after 24 h due to the unbalanced ramification and the colony no longer increases its size.
Keywords: Species Specificity; houby; Pigments, Biological; druhová specificita; Antifungal Agents; Fungi; biologické pigmenty; antifungální látky